Strategy for Developing Numeracy Skill of Elementary School Students Based on Constructivism Theory - I Komang Sesara Ariyana; I Putu Suardipa (International Conference on Elementary Education, 2023)
The purpose of this study is to analyze strategies that can be used to develop numeracy skills of elementary school students based on constructivism theory. This research is included in library research. Library research is research with a qualitative approach. The data in this study are qualitative data obtained from various sources such as scientific journal articles, books, and policies related to the development of elementary school students' numeracy skills. The object of this research is the strategies that can be done by elementary school mathematics teachers related to the development of students' numeracy skills that refer to constructivism theory. The data analysis technique was carried out through four stages, namely collecting data, reducing data, displaying data, and drawing conclusions. This library research will discuss (1) constructivism theory in learning mathematics, (2) elementary school students' numeracy skills, and (3) elementary school students' numeracy skills development strategies based on constructivism theory.